2019
DOI: 10.1115/1.4041989
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Nozzle Spacing Effects on Characteristics of Round Twin Free Jets

Abstract: The objective of this research is to investigate the effects of nozzle spacing on the mean velocity and higher order turbulent statistics of free round twin jets produced from sharp contraction nozzles. The experiments were performed in an air chamber for four nozzle spacing ratios, S/d = 2.8, 4.1, 5.5 and 7.1 and at a fixed Reynolds number of 10,000. A planar particle image velocimetry system was used to conduct the velocity measurements. The results show that downstream of the potential core, a reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 49 publications
1
12
1
Order By: Relevance
“…For the experiments of Harima et al (2001), U 0 /U j = 1/(0.98S/d + 0.27) and L 0 /d = 5.6S/d − 0.31. Laban et al (2019) had performed experiments on twin round jets with S/d = 2.8, 4.1, 5.5 and 7.1 at Re = 10 000. They have provided the maximum mean velocity on the centreline and the distance to the location (U 0 and L 0 in our notation).…”
Section: Nozzle Spacing Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the experiments of Harima et al (2001), U 0 /U j = 1/(0.98S/d + 0.27) and L 0 /d = 5.6S/d − 0.31. Laban et al (2019) had performed experiments on twin round jets with S/d = 2.8, 4.1, 5.5 and 7.1 at Re = 10 000. They have provided the maximum mean velocity on the centreline and the distance to the location (U 0 and L 0 in our notation).…”
Section: Nozzle Spacing Effectsmentioning
confidence: 99%
“…Particle image velocimetry data for water jets with S/d = 1.5, 2.0, 3.0 at Re = 3300 are also available (Zang & New 2015). The most recent measurements were reported in Laban et al (2019). The round jets were at Re = 10 000 and S/d = 2.8, 4.1, 5.5, 7.1.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the converging region of continuous slotted jets is characterized by the presence of a time-averaged bubble region, as opposed to continuous twin jets where no reverse flow has been detected so far, as documented by the literature review in the research paper by Laban et al [29]. Conversely, recent experimental works have demonstrated that double-orifice synthetic jets present a recirculation region between its orifices [21]; the present study, along with the findings of the cited one, can shed light on the occurrence of this inner reverse flow region for synthetic jets, also by relating phaseand time-averaged results.…”
Section: Time-averaged Resultsmentioning
confidence: 98%
“…For the formation and characteristics of a free jet, the diffuser is of key importance [23], [24], [25], [26], [27]. Studies by Hussein et al [28] or [29], or by Mi et al [30] are among the papers dedicated to the geometry of a jet generated by a round diffuser. On the other hand, examples of analyses dedicated to a rectangular nozzle include [31] or [32].…”
Section: Introductionmentioning
confidence: 99%